Examining the effects of fiscal decentralization and income inequality on the economic performance of west Sumatra province, Indonesia - Eva Herianti; Amor Marundha (Global Business & Finance Review (GBFR), 2024)
Purpose: The issue of income inequality in various regions of Indonesia is a significant national concern that requires immediate attention. Despite the government's efforts through fiscal decentralization policies, inequality persists. This study decisively explores the impact of fiscal decentralization and regional income inequality on regional financial performance. Design/methodology/approach: The research sample comprises 19 districts/cities in West Sumatra province, with data from 2018 to 2020 sourced from the Ministry of Finance and the Central Statistics Agency of West Sumatra Province. The analytical approach utilized in this study is the SmartPLS ver 3.2 model. Findings: The first research finding indicates that fiscal decentralization has a positive and substantial impact on regional financial performance. A second finding suggests that regional income inequality also positively and significantly affects regional economic performance. Research limitations/implications: These results enrich the perspective of Rostow's stages of economic growth model from a different standpoint. Originality/value: This study contributes to a deeper comprehension of the fields of economics, politics, and social sciences, particularly within the specific context of the province of West Sumatra in Indonesia.
Keywords: 650; Fiscal Decentralization; Income Inequality; Rostow Model; West Sumatera